Role of Temporary Accounting Distortions in Reducing Persistence of Accruals - Javad Rezazadeh (Shahid Bahonar University of Kerman, 2011)
Following Sloan (1996), numerous studies document that the accrual component of earnings is less persistent than the cash flow component of earnings. Some intelligent specialists argue that accounting distortions cause lesser persistence of accrual component of earnings. Others attribute the latter to economic indices such as growth of firms. This study consider the role of accounting distortions in lower persistence of accruals by analyzing data from the firms listed in Tehran Stock Exchange during 1377 to 1387. Our evidence shows that accounting distortion is the important factor in lower persistence of accruals. Moreover, results show that growth of sales reduces accruals persistence, and that efficient use of assets increase accruals persistence.